(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. The patients with non-dipper hypertension have an increased risk for target organ damage because of inflammation and platelet activation. In this study, we aimed to investigate the association between ambulatory blood pressure monitoring (ABPM) values and inflammation with platelet indices in children with dipper and non-dipper hypertension. Materials and Methods. A total of 153 patients who underwent ABPM were included in this retrospective study. The participants were divided into three groups (61 non-dipper hypertensive, 28 dipper hypertensive, 64 normotensive). Neutrophil and platelet count, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), mean platelet volume (MPV), plateletcrit (PCT), and platelet distribution width (PDW) were matched data among groups. Results. The neutrophil counts were higher in the non-dipper and dipper groups compared with the normotensive group (P < .05, P < .05, respectively). Also, MPV levels were significantly higher in the non-dipper and dipper groups than in normotensive group (P < .05, P < .05, respectively). Logistic regression analysis showed significant association between non-dipper status and MPV with platelet count (P < .05, P < .05, respectively). The abilities of MPV and platelet count to predict the non-dipper status were determined by receiver operating characteristic curve analysis (areas under the curve were 0.709 and 0.604, respectively). Conclusions. The higher MPV and neutrophil count may be potential indicators of increased risk for the development of hypertension in children. In addition, MPV and platelet count may help to determine the presence of non-dipper status in children with hypertension.